The influence of drop height on ground reaction forces in mountain biking - Phillips, K. C.; Kilgas, M. A.; Jensen, R. L. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
This study examined ground reaction forces (GRFs) when landing from a drop-off in mountain biking. Eight male mountain bikers participated in this study. Participants rode up onto and across an adjustable wooden platform, performing three drop maneuvers at each vertical height of 29 cm, 48 cm, and 67 cm, simulating drop-offs in mountain biking. Peak vertical GRFs when landing from each drop was measured using 3 force platforms in the landing area. When examining the rear and front tire individually, peak vertical GRFs were significantly higher for the rear tire at each drop height. Additionally, significant increases in summed peak vertical GRFs occurred from the low to middle and middle to high dropoff. Therefore, this may support implications that mountain biking includes osteogenic stimuli that is beneficial to bone health.